EMPLOYEE PERFORMANCE IN THE CULINARY BUSINESS SECTOR: THE INFLUENCE OF WORK MOTIVATION, WORK ENVIRONMENT, AND WORKLOAD - Rodohtul Hidayah; Aldi Pranata; Agung Priyono; Narti Eka Putri (Journal of Management and Leadership, 2026)
This study aims to examine the effects of work motivation, work environment, and workload on employee performance at CV Legenda Kuliner Legendaris. A quantitative research approach with a survey method was employed. The study involved 77 employees selected through a saturated sampling technique, in which the entire population was used as the research sample. Data were collected using a Likert-scale questionnaire and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) with SmartPLS software. The results indicate that work motivation has a positive but insignificant effect on employee performance. In contrast, both work environment and workload have positive and significant effects on employee performance. Workload was found to be the most influential variable affecting employee performance. The coefficient of determination (R²) value of 0.852 indicates that work motivation, work environment, and workload collectively explain 85.2% of the variance in employee performance, while the remaining 14.8% is influenced by other factors outside the research model. These findings suggest that organizations should prioritize the improvement of the work environment and effective workload management to enhance employee performance.